Medelssohn Musical Institute; Consulting Engineer; Children's Carriages - Sampson, Davenport, & Co. (Tufts Archival Research Center, 2005)
Page image of Medelssohn Musical Institute; Consulting Engineer; Children's Carriages from the 1870 Boston City Directory